Creating Multimedia Content for Prevention of Covid 19 Virus Transmission in the tradisional market - Riwinoto Riwinoto; Selly Artaty Zega; Evaliata BR Sembiring; Afdhol Dzikri; Gendhy Dwi Harlyan; Happy Yugo Prasetya; Arta Uly Siahaan; Cahya Miranto; Ardiman Firmanda; Ahmad Saropi; Melsha Haq Zulfikar; Weimpy Ocastian; Gunawan Humiras Pangestu Nababan; David Hasmito Tanbari; Novi Anggraeni; Ica Yolanda; Diella Marfika Tama; Muhammad Ikhlas Habibi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
The COVID-19 pandemic outbreak has caused difficulties for the community, for example official trips, tours, shopping, watching films and others, which in turn caused the general economy to decline. This is what makes lecturers, workers and students in the multimedia field take the initiative to make or develop multimedia products that have educational value to the public about the prevention of the Corona virus. One of the places that is the central point of the spread of the Corona virus is the market because the market is a meeting place for people who have an interest in buying and selling if one person is infected with Corona, the virus can spread to the community around the market. Therefore, the product we have developed is a multimedia product that contains educational materials for Corona virus prevention on the market. These products are community services and educational games, comic posters, motion graphics, video advertisements. The results of internal testing to students and external testing to communities related to traders show that comic media is best used in spreading service messages to the community.